Multiple myeloma treatment strategies with novel agents in 2011: a european perspective - Ludwig, Heinz; Beksac, Meral; Bladé, Joan; Cavenagh, Jamie; Cavo, Michele; Delforge, Michel; Dimopoulos, Meletios; Drach, Johannes; Einsele, Hermann; Facon, Thierry; Goldschmidt, Hartmut; Harousseau, Jean‐Luc; et al. (The oncologist, 2011)
The arrival of the novel agents thalidomide, bortezomib, and lenalidomide has significantly changed our approach to the management of multiple myeloma and, importantly, patient outcomes have improved. These agents have been investigated intensively in different treatment settings, providing us with data to make evidence‐based decisions regarding the optimal management of patients. This review is an update to a previous summary of European treatment practices that examines new data that have been published or presented at congresses up to the end of 2010 and assesses their impact on treatment practices.
Gesehen am 11.11.2022